Climate change and global equity - Ackerman, Frank (Anthem environmental studies., 2014)
Ambitious measures to reduce carbon emissions are all too rare in reality, impeded by economic and political concerns rather than technological advances. In this timely collection of essays, Frank Ackerman and Elizabeth A. Stanton show that the impact of inaction on climate change will be far worse than the cost of ambitious climate policies.